Pragmatics - Susi Herti Afriani (Fakultas Adab dan Humaniora UIN Raden Fatah, 2013)
Abstracs:This paper aims to explain the importance of pragmatic areas to be studied in the development of teaching materials, the teaching of linguistics. To that end, I began this paper with a discussion of the linguistics understanding, pragmatics understanding, briefly explain topics development, and, by looking at the difference in studies with another fields in linguistics, showing the importance of pragmatics.The experts define the term pragmatics differently. Pragmatics grows from four trends or tradition, namely: (1) the tendency of insyntaxsism, (2) socio-critical tendencies, (3) the philosophical tradition, and (4) ethnometodology tradition. Topics include discussion of the pragmatics; they are speech acts theory, cooperative principles, implicature, relevance theory, and the theory of politeness. In conclusion, I see the importance of pragmatics in linguistics at least two things: first, pragmatics is the only level in linguistics which studies language by taking into account also users and secondly, relates to the inability of syntax and semantics to explain the phenomenon of the use of everyday language, I concluded that semantics and pragmatics look at the position as two complement each other. Furthermore, with regard to the teaching of language, pragmatics plays a role in the development of communicative competence. Key words: Teaching Materials Development, Pragmatics, Linguistics